HUBUNGAN TINGKAT PENDIDIKAN DENGAN KINERJA GURU PAUD DALAM MENGAJAR DI DESA PANDAU JAYA KECAMATAN SIAK HULU KABUPATEN KAMPAR - Lathifah Fitriani Syah; Ria Novianti; Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The purpose of this study is to determine the level of teacher education, and teacher performance, and the relationship between the level of education with the performance of early childhood teachers in Desa Pandau Jaya Kecamatan Siak HuluKabupaten Kampar. This survey was conducted on 52 PAUD teachers in Desa Pandau Jaya, Kecamatan Siak Hulu Kabupaten Kampar. The method used is correlation research. Data collection tools used are data and questionnaire techniques. From the result of data analysis from percentage of education level equal to 46,2% high school educated teacher included in high category, and percentage of PAUD teacher performance in teaching equal to 30,8% in high category. From the data analysis obtained value of each variable of 4.564, obtained Kai Square Value (Chi Square) of 452,74. While the value of contingency coefficient of = 0,300. Because the value of Contingency Coefficient (Cramer) of 0.300 which lies in the range of 0.20 s / d ≤ 0.40 with the low category, but definitely. So it can be concluded that there is no relationship between teacher education level with the performance of early childhood teachers in teaching but in the low category.Keywords: Level of education, Teacher’s performance